A Critical Review on Nidra as a Cardinal Requisite for Optimal Health and Well Being - Sharma, Raksha; Bhojani, Meera K (International Research Journal of Ayurveda & Yoga, 2023)
Ayurveda as a holistic science lays great emphasis on lifestyle modification under Ahar (Diet), Vihar (Daily regimen) and Aoushadh (triad for prevention and treatment of all diseases).Among vihara nidra is considered as a very influencing factor in Ayurveda classics. Nindra is considered as one of the sub pillar of Trayopasthambh which includes Ahaar, Bhramcharya, and Nidra. Ahaar nourishes our body, Brahmcharya nourishes mind but Nidra nourishes both body and mind. Sleep maintains the functions of entire body through homeostasis; contemporary science states that NREM (non rapid eye movement) sleep may be state of brain repair i.e. of increased cerebral protein synthesis or of reprogramming the brain so that the information achieved in a wakeful functioning is most efficiently assimilated. Ayurveda substantiates the similar opinion by designating it as ‘Bhut-Dhatri ‘which nourishes the all living beings.